Analisa Dampak Penyembahan Berdasarkan Yohanes 4:23 pada Pertumbuhan Rohani Jemaat GBI Patuha Bandung - Adi Darta; Tonny Andrian Stefanus; Ester Yunita Dewi (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
The thesis entitled, "Analysis of the Impact of Worship Based on John 4:23 on the Spiritual Growth of the GBI Patuha Bandung Congregation."John 4:23 can provide the teachings of the Lord Jesus about worship and the extent of its impact on the spiritual growth of the congregation. The research aims to explore how worship in the context of church services affects spiritual growth, including heart transformation, spiritual renewal, and character development in Christ. This study uses a qualitative descriptive approach to analyze the impact of worship based on John 4:23 on the spiritual growth of the congregation at Gereja Bethel Indonesia (GBI) Patuha, Bandung. Data were collected through interviews with leaders, activists, and church workers, as well as direct observations in the field. The results show that worship, as described in John 4:24, is a vital aspect of the spiritual life of the GBI Patuha congregation. The church has undergone significant transformation by shifting its focus from teaching to worship, with the aim of deepening a personal relationship with God. Worship is not only an emotional activity but also a means to strengthen faith, renew the spirit, and shape Christ-like character in the lives of the congregation. Worship grounded in the Word of God and the guidance of the Holy Spirit positively impacts the church community, encouraging active service and devotion to God and others. The congregation experiences heart transformation and spiritual renewal, which strengthens their relationship with God. Furthermore, worship focused on God encourages the congregation to live in humility, love, and obedience, as well as increasing their enthusiasm for serving. Innovations such as providing digital worship platforms also extend the church’s reach and enhance congregational involvement. This study also recommends the development of more structured worship training to deepen theological understanding and correct worship practices according to biblical principles.